Socio-Cultural Issues In Agricultural Modernization: A Case Study of the Food Estate Program in Pulang Pisau Regency - Mahardika, Ode; Azkar, Nurul; Sopiana, Yunita (International Journal of Multidisciplinary Approach Research and Science, 2024)
The food estate program located in Pulang Pisau Regency, Central Kalimantan Province, focuses on the development of the agricultural sector. However, research using a qualitative approach has found that the increase in rice production in Pulang Pisau Regency, as an outlying area, is inversely proportional to the high price of rice in Palangkaraya City, the core or central area of activities in Central Kalimantan Province. This occurs because the rice production in Pulang Pisau Regency is directly bought by traders, who generally come from South Kalimantan. The rice is then processed in South Kalimantan and resold in the form of premium quality rice to Palangkaraya City. The Dayak culture of the indigenous population of Central Kalimantan, which lacks trading culture, provides an opportunity for the Banjar people, who have long been known as traders. As a result, although rice production in Pulang Pisau Regency increases, the price of rice remains high in Palangkaraya City due to the long production and distribution costs.